A NATIONALISM AND POWER POLITICS ON BALKAN - Jorma, Atilla (International Scientific Journal Vision, 2019)
Before the Ottomans the Bulgars were the most important Turkic community on Balkan. They were also the only ones who formed a state. Bulgaria stayed as a toponym also when those people were disappeared. Meanwhile, were they assimilated and with whom is total another question. In any case four century passed without any sign or mention of them as a crowd. Just in the era of romantic nationalism those ancientpeople were found in history and were used for building a new nation. Those tendencies however were intermixed with politics of the superpowers.